Working conditions, authorizations, mental health, and job satisfaction of physician assistants in Germany - Treusch, Yvonne; Möckel, Luis; Kohlstedt, Karin (Frontiers in Public Health, 2023)
Objective This study explores associations among the overall and facet-specific job satisfaction, work-related factors, responsibilities, and mental health of physician assistants (PAs) in Germany to identify factors that prolong the lifetime and wellbeing of PAs in practice and to counteract the shortage of healthcare staff. Methods An online survey comprising sociodemographic and work-related items, items from the short questionnaire of general and facet-specific job satisfaction (KAFA), and the Depression, Anxiety, and Stress Scale (DASS-21) were distributed to PAs working in Germany in 2021 (cross-sectional survey design). Descriptive statistics, DASS-21 subscale score analysis, t-test, ANOVA, or Kruskal–Wallis test was used. Results PAs (n = 169) were working mainly in surgery (23.2%), internal medicine (20.3%), or orthopedics and trauma surgery (17.5%), whereas only a few PAs were working in emergency care, geriatrics, neurology, or oncology. They were responsible for a broad spectrum of medical activities depending on the practice setting. PAs working in emergency care claimed to be the most empowered, followed by PAs in orthopedics and surgery. Almost all PAs carried out documentation, anamnesis, and diagnostic services. Although almost all PAs rated their overall job satisfaction as good, satisfactory, or pleasant (91.6%), single facets of job satisfaction were rated differently. Colleagues and supervisors were assessed very positively, whereas payment and professional activities were rated rather average and development opportunities even worse. PAs working in oncology demonstrated the highest overall job satisfaction, followed by PAs working in geriatrics and emergency care. Overall job satisfaction was significantly negatively associated with depression, anxiety, and stress scores (p ≤ 0.001, p ≤ 0.05, and p ≤ 0.05, respectively). Particularly, female gender, having an urban residence, and PAs working in oncology demonstrated significantly increased anxiety scores. Moreover, depression scores of PAs working in oncology or neurology or with a low net income exceeded critical cutoff values. Conclusion Interventions aimed at removing the significant negative correlation among job satisfaction, depression, anxiety, and stress scores are needed. To retain PAs in their jobs, salary, autonomy, and development opportunities should be improved and prevention programs for anxiety and depression should be offered. Remarkably, PAs' overall good job satisfaction was mainly determined by good evaluations of supervisors and colleagues.